STEVENS-JOHNSON SYNDROME DUE TO ADVERSE DRUG REACTIONS: A CASE SERIES - ANSARI, ZAFAR MASOOD; SRIVASTAVA, BHAVANA; ROHATGI, ARUNIMA; JOSHI, KALPANA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Stevens-Johnson syndrome (SJS) is a rare, serious disorder affecting skin and mucous membranes. It is one of the few serious dermatological adverse effects of drugs encountered in clinical practice which is characterized by blisters and rash on skin, mucous membranes, swelling over face and lips, and hyperpigmentation. After that, the outer layer of affected skin becomes dead, sheds, and starts to heal after several days of inflicting injury. Here, we present a case series of ofloxacin and chloroquine induced SJS after the consent given by patients. First case is a 62 years old male received Ofloxacin and second patient is a 40 years old male received chloroquine. Both patients experienced a severe skin reaction which was diagnosed as SJS. The above-mentioned medications will be implicated in cases of SJS. We should prescribe these medications with extreme caution.